Understanding consumer buying behavior towards fast food restaurant in Kota Samarahan / Nurul Atiqah Jamil - Jamil, Nurul Atiqah (2015)
Consumer buying behavior is considered to be an Inseparable part of marketing and Kotler and Keller (2011) stated that consumer buying behavior is the study of the ways of buying and disposing of goods, services, ideas or experiences by the individuals, groups and organizations in order to satisfy their needs and wants. Alternatively, consumer buying behavior "refers to the buying behavior of final consumers, both Individuals and households, who buy goods and services for personal consumption" (Kumar, 2010). From marketers' point of view issues specific aspects of consumer behavior that need to be studied include the reasons behind consumers making purchases, specific factors influencing the patterns of consumer purchases, analysis of changing factors within the society and others.